The relationships between somatic constitution, physical fitness, school achievements and fish products consumption in junior male and female high school students - Zurek, Grzegorz; Sarna, Michal; Przednowek, Karolina; Delaunay, Gerda (Technium Social Sciences Journal, 2020)
Easily digestible and low-calorie fish products are important components of a proper human diet. The main aim of the study was to assess the relationship between somatic constitution, physical fitness and school grades and the consumption of fish products by junior high school students . The research was carried out at Junior High Schools No. 8 and 9 in Rzeszów, in the school year 2014/2015. The mean age of examined girls was 13.96 ± 0.26, and boys - 13.97 ± 0.31 years. 118 students (58 girls and 60 boys) participated in the study. Basic somatic parameters were measured and tests concerning motor skills from the Eurofit test were performed. A short survey on the consumption of fish products by students was conducted and information on the results of junior high school final exams were obtained. The research showed that boys who have not consumed any fish products or had them rarely in their diet featured a taller body height. The opposite phenomenon was observed in the population of girls. In the group of boys, better exam results in selected subjects were achieved by those consuming fish less often, i.e. once a week or not at all. In the case of the females this phenomenon is only observed in relation to the exam in the school subject called Nature. The analysis of variance carried out in terms of the frequency of fish consumption showed that depending on the amount of fish products in the respondents’ diet, the gender significantly differentiates the level of physical fitness of examined girls and boys (except for tapping).